UNDERSTANDING EFL STUDENTS’ MOTIVATION TO LEARN: WHY DO YOU STUDY ENGLISH? - Nuraeni Nuraeni; Sitti Aisyah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
This research explored students’ motivation to learn English as a foreign language. The aim of this research was to find out what kind of motivation underlie their decision to choose English as their major. This research is important as it can be used as an assist for students to be aware of their own motivation to learn as well as a basis for teachers in helping students to improve students’ learning motivation. To reach the goal of the research, an interview was carried out. The result showed that from the data, initially, most students had extrinsic motivation and only a few students experienced intrinsic motivation. After learning English for more than a year, the motivation of some students mostly stayed the same. However, some students changed their motivation. Due to difficulties in learning, several students who were motivated to learn English intrinsically turned into extrinsic motivation. Oppositely, one student coined her extrinsic motivation attributable to her curiosity into intrinsic motivation and found that English is an interesting subject to learn